Olasılık Konusunun Öğrenilmesini Zorlaştıran Nedenler Hakkında Ortaokul Matematik Öğretmenlerinin Görüşleri - Gürbüz, Ramazan; Erdem, Emrullah (Muş Alparslan Üniversitesi, 2017)
This study aims at examining the reasons making learning the subject ‘probability’ difficult in view of secondary school mathematics teachers. The study was carried out with 38 secondary school mathematics teachers working in different schools located in a city of Turkey. Data were collected by means of a form consisting of two open-ended questions. The data were analyzed and codes from the data, three sub-themes and one main theme from codes were obtained by using content analysis technique. As a result of the analysis, evidence was found that the reasons arised from student (negative attitude, lack of prior knowledge, not being associated with daily life, insufficient reasoning, misconceptions), from teacher (lack of knowledge and inexperience, negative attitude, inability to use appropriate teaching strategies) and from some other factors (abstractness of the subject, age, crowded classrooms, exam-based teaching).

Bu çalışmanın amacı, ortaokul matematik öğretmenlerinin olasılık konusunun öğrenilmesini zorlaştıran nedenlere ilişkin görüşlerini belirlemektir. Çalışma grubu, Türkiye’nin bir ilindeki farklı okullarda görev yapan 38 ortaokul matematik öğretmeninden oluşmaktadır. Araştırmanın verileri, iki açık uçlu sorudan oluşan bir form vasıtasıyla toplanmıştır. Elde edilen verilerin içerik analizi yapılarak, verilerden kodlar, kodlardan üç alt tema ve bir ana tema elde edilmiştir. Yapılan analizler sonucunda, olasılık konusunun öğrenilmesini zorlaştıran nedenlerin öğrenciden (olumsuz tutum, yetersiz önbilgi, günlük hayatla ilişkilendirememe, yetersiz muhakeme, kavram yanılgıları), öğretmenden (bilgi ve tecrübe eksikliği, olumsuz tutum, uygun öğretim stratejisi kullanılmaması) ve diğer bazı nedenlerden (konunun soyut olması, yaşın etkisi, sınıfların kalabalık olması, sınav odaklı öğretim) kaynaklandığı ortaya çıkarılmıştır.
Middle School Mathematics Teachers’ Views on the Challenging Reasons for Learning of Probability Subject
anemon
Keywords: Mathematics Teaching; Probability; Views of Middle School Mathematics Teachers; Difficulty; Matematik Öğretimi; Olasılık; Ortaokul Matematik Öğretmeni Görüşleri; Zorluk